Species-Specific Detection and Identification of Fusarium Species Complex, the Causal Agent of Sugarcane Pokkah Boeng in China - Lin, Zhenyue; Xu, Shiqiang; Que, Youxiong; Wang, Jihua; Comstock, Jack C.; Wei, Jinjin; McCord, Per H.; Chen, Baoshan; Chen, Rukai; Zhang, Muqing (PLOS ONE, 2014)
Background Pokkah boeng disease caused by the Fusarium species complex results in significant yield losses in sugarcane. Thus, the rapid and accurate detection and identification of the pathogen is urgently required to manage and prevent the spreading of sugarcane pokkah boeng. Methods A total of 101 isolates were recovered from the pokkah boeng samples collected from five major sugarcane production areas in China throughout 2012 and 2013. The causal pathogen was identified by morphological observation, pathogenicity test, and phylogenetic analysis based on the fungus-conserved rDNA-ITS. Species-specific TaqMan real-time PCR and conventional PCR methods were developed for rapid and accurate detection of the causal agent of sugarcane pokkah boeng. The specificity and sensitivity of PCR assay were also evaluated on a total of 84 isolates of Fusarium from China and several isolates from other fungal pathogens of Sporisorium scitamineum and Phoma sp. and sugarcane endophyte of Acremonium sp. Result Two Fusarium species (F. verticillioides and F. proliferatum) that caused sugarcane pokahh boeng were identified by morphological observation, pathogenicity test, and phylogenetic analysis. Species-specific TaqMan PCR and conventional PCR were designed and optimized to target their rDNA-ITS regions. The sensitivity of the TaqMan PCR was approximately 10 pg of fungal DNA input, which was 1,000-fold over conventional PCR, and successfully detected pokkah boeng in the field-grown sugarcane. Conclusions/Significance This study was the first to identify two species, F. verticillioides and F. proliferatum, that were causal pathogens of sugarcane pokkah boeng in China. It also described the development of a species-specific PCR assay to detect and confirm these pathogens in sugarcane plants from mainland China. This method will be very useful for a broad range of research endeavors as well as the regulatory response and management of sugarcane pokkah boeng.